Visceral obesity and psychosocial stress: a generalised control theory model. Issue 3 (2nd July 2016) - Wallace, Rodrick
ABSTRACT: The linking of control theory and information theory via the Data Rate Theorem and its generalisations allows for construction of necessary conditions statistical models of body mass regulation in the context of interaction with a complex dynamic environment. By focusing on the stress-related induction of central obesity via failure of HPA axis regulation, we explore implications for strategies of prevention and treatment. It rapidly becomes evident that individual-centred biomedical reductionism is an inadequate paradigm. Without mitigation of HPA axis or related dysfunctions arising from social pathologies of power imbalance, economic insecurity, and so on, it is unlikely that permanent changes in visceral obesity for individuals can be maintained without constant therapeutic effort, an expensive – and likely unsustainable – public policy.